2013
DOI: 10.1590/s0100-29452013000200005
|View full text |Cite
|
Sign up to set email alerts
|

Gas exchange, phisiological indexes and ionic accumulation in Annona emarginata (Schltdl.) H. Rainer seedlings in nutrients solution

Abstract: "Araticum-de-terra-fria" (Annona emarginata (Schltdl.) H. Rainer) has been consider a good alternative in rootstock production for the main commercial Annonaceae species. Although this species develops in different soil and climate conditions, there is no understanding by the physiological responses of this species at different nutritional levels. Thus, the objective of this study was to evaluate the influence of different ionic strengths on development of vegetative species known as "Araticum-de-terra-fria". … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The propagation method most used in Annonaceae is grafting, in which one rootstock is formed from seeds (BARON et al, 2013, LEMOS et al, 2013. Thus, it is a constant search for alternative species such as Annona diversifolia Saff and Annona purpurea Moc & Sessé ex Dunal, that are potential species to be used in the expansion of production areas as rootstock to other Annonaceous, so as for in natura consumption, food industry or to discoveries of new molecules for pharmaceutical industry (LUNA-CAZARES et al, 2006;LOBO et al, 2007;DE-LA-CRUZ et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The propagation method most used in Annonaceae is grafting, in which one rootstock is formed from seeds (BARON et al, 2013, LEMOS et al, 2013. Thus, it is a constant search for alternative species such as Annona diversifolia Saff and Annona purpurea Moc & Sessé ex Dunal, that are potential species to be used in the expansion of production areas as rootstock to other Annonaceous, so as for in natura consumption, food industry or to discoveries of new molecules for pharmaceutical industry (LUNA-CAZARES et al, 2006;LOBO et al, 2007;DE-LA-CRUZ et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It justifies the higher E in plants with higher water availability detected in this study. We observed that carbon assimilation (C i ) values did not coincide with the alterations of g s and E. It indicates that, despite the stomatal opening, there was no increase in CO 2 input in leaves, which can be explained by changes in the photosynthetic apparatus due to water or nutrient availability for plants (Baron et al 2013). Photosynthesis is not only related to stomatal limitations but also nonstomatal limitations, such as the diffusion of CO 2 from intercellular spaces to the chloroplasts and biochemical limitations to photosynthetic efficiency (Salmon et al 2020).…”
Section: Gas Exchangementioning
confidence: 74%
“…The experimental design was a randomized block with four blocks, each one with four plants. The cultivation was done in a greenhouse and Hoagland and Arnon n°2 was applied, diluted to 50% of its ionic strength, electrical conductivity (EC) of 1.0 miliSiemens cm -1 (300 ml per pot) and pH 5.5-6.5, according to Baron et al (2013).…”
Section: Methodsmentioning
confidence: 99%